Investigation of raman spectrum, structural, morphological, and optical features of Fe2O3 and Fe2O3/reduced graphene oxide hybrid nanocomposites. (1st December 2022) - Abdel-Salam, Ahmed I; Gomaa, Islam; Khalid, A; Soliman, T S
Abstract: The Hematite (Fe2 O3 ) nanoparticles and Fe2 O3 -reduced graphene oxide (rGO) nanocomposite were successfully synthesized via co-precipitation method. The rGO was used as passivation layer to improve the optical properties of the Fe2 O3 . X-ray diffraction, transmission electron microscopy, Raman, and Fourier transform-infrared spectroscopy were used to investigate the modification in the Fe2 O3 structure in the presence of rGO. UV-visible absorption spectra were investigated, and the optical bandgap was determined. Using different relations like Moss, Rivandra, Anani, and others, the refractive index was calculated depending on the obtained optical bandgap. The refractive index values were compared with the data calculated from Duffy relation and good accordance was found between them. The optical bandgap and electronegativity were found to decrease by the addition of rGO in Fe2 O3 matrix, while the refractive index was found to increase. Consequently, the Fe2 O3 -rGO nanocomposites capacity to control optical properties makes it a perfect contender for a variety of applications.